The lifetime production of Bovec and Improved Bovec sheep breeds - Gregor Gorjanc; Vesna Gantner; Dragomir Kompan (Mljekarstvo)
Production data of Bovec and Improved (with East-Friesian) Bovec sheep born between years 1989 and 2006 were used for the analysis of culling dynamics and lifetime production. Lifetime production was calculated as the sum of production at each lambing (number of born and liveborn lambs and litter birth weight), weaning (number of weaned lambs and litter weaning weight) or during each lactation (milk yield, fat (6.5 %) and protein (5.8 %) corrected milk yield (FPC; Pulina et al., 2005.), and fat and protein yield) for culled sheep. Animals with any missing records from the first till the last lambing, weaning or lactation were removed from the analysis. Animals that left the system of animal recording alive, due to selling or the cancellation of recording by a breeder were also excluded. Dataset included records for 2254 sheep: 1734 of Bovec and 520 of Improved Bovec breed. Data preparation and statistical analysis were performed with the use of a statistical program R (R Development Core Team, 2007.) and additional packages Zelig (Imai et al., 2007; Bailey and Alimadhi, 2007; Imai et al., 2008) and lme4 (Bates and DebRoy, 2004; Bates, 2007). Results have shown that in the period ≤1996 Bovec breed had on average 4.4 lactations in their lifetime, which was almost one lactation more than in Improved Bovec breed. In the period after the year 1996 the highest proportion of animals were culled in the first lactation (as expected due to culling dynamics), with slightly higher proportion in Improved Bovec breed than in Bovec breed. Lifetime number of born, liveborn and weaned lambs was higher for about one lamb in Improved Bovec breed. Lifetime lamb weight gain did not differ between breeds, due to the high frequency of early weaning in Improved Bovec breed. During lifetime, Improved Bovec sheep produced around 200 kg (~34 %) more milk, around 190 kg (~32 %) more FPC milk, around 12 kg (~32 %) more milk fat, and around 10 kg (~34 %) more milk protein than Bovec breed. However, if the mean metabolic weight of breeds is taken into account the difference in milk production amounts to only ~6 % (~2 % for FPC milk). These results show that Bovec breed has satisfactory milk production, but too low body weight for intensive milk production. On the other hand, low body weight makes this breed suitable for extensive farming in hill and mountain areas. Improved Bovec breed has good results in Slovenian conditions, due to the similarity of environmental conditions with East Friesian’s country of origin.